2023
DOI: 10.7759/cureus.38222
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Metformin-Associated Lactic Acidosis

Abstract: Metformin is a US FDA-approved oral anti-hyperglycemic medication used to treat non-insulin-dependent diabetes mellitus (NIDDM). Metformin, a biguanide drug, works by reducing glucose production in the liver, decreasing intestinal absorption, and improving insulin sensitivity, leading to lower blood glucose levels. Metformin is generally considered to be a medication with a good safety profile and high tolerability. However, metformin therapy is associated with an uncommon but potentially serious complication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…As is known, the protein transporters involved are expressed differently in human tissues and have high genetic polymorphism, generating wide inter-individual variability in metformin pharmacokinetics, explaining the range of dosage and different antidiabetic effectiveness [ 87 , 88 , 90 ]. The detected C max is around 1 µg/mL, and, in general, the optimal plasma concentration should be less than 2 µg/mL, whereas concentrations greater than 5 µg/mL are considered unsafe due to the increased risk of severe adverse effects, such as lactic acidosis [ 87 , 91 , 92 ]. However, several authors reported blood concentrations of up to 80 µg/mL in subjects treated with metformin, showing high variability in the pharmacokinetics of this drug [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As is known, the protein transporters involved are expressed differently in human tissues and have high genetic polymorphism, generating wide inter-individual variability in metformin pharmacokinetics, explaining the range of dosage and different antidiabetic effectiveness [ 87 , 88 , 90 ]. The detected C max is around 1 µg/mL, and, in general, the optimal plasma concentration should be less than 2 µg/mL, whereas concentrations greater than 5 µg/mL are considered unsafe due to the increased risk of severe adverse effects, such as lactic acidosis [ 87 , 91 , 92 ]. However, several authors reported blood concentrations of up to 80 µg/mL in subjects treated with metformin, showing high variability in the pharmacokinetics of this drug [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other side effects commonly reported are headache, dizziness, fatigue, pruritus, and dysgeusia [ 233 , 234 ]. One of the most feared adverse reactions to metformin treatment is lactic acidosis, which is a rare event with an incidence of 1 in 30,000 patients but can lead to fatal outcomes [ 91 , 235 ]. Generally, the observed cases occurred in patients who received high doses and/or had severe hepatic and renal impairment, old age, and alcoholism [ 236 , 237 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with lactate concentrations >4 mmol/L, in the absence or presence of hypotension, have a higher in-hospital mortality than patients with intermediate (2–3 and 3–4 mmol/L) or normal lactate concentrations ( Casserly et al, 2015 ). Metabolic acidosis can induce confusion, malaise and lethargy and thereby resemble septic encephalopathy ( Cruz-Flores, 2021 ; Mahmood et al, 2023 ).…”
Section: Indicators Of Sepsis and Septic Encephalopathymentioning
confidence: 99%
“…Metformin does not, however, come without adverse effects. In rare instances, prolonged usage of the medication can result in lactic acidosis and gastrointestinal problems 15 . Finding complementary or alternative therapy is therefore essential to improving the management of diabetes.…”
Section: Introductionmentioning
confidence: 99%